Advanced glycation end products modulate electrophysiological remodeling of right ventricular outflow tract cardiomyocytes: A novel target for diabetes‐related ventricular arrhythmogenesis. Issue 21 (2nd November 2022) - Chen, Yao‐Chang; Lu, Yen‐Yu; Wu, Wen‐Shiann; Lin, Yung‐Kuo; Chen, Yi‐Ann; Chen, Shih‐Ann; Chen, Yi‐Jen
Abstract: Diabetes mellitus is associated with cardiovascular disease and cardiac arrhythmia. Accumulation of advanced glycation end products closely correlates with cardiovascular complications through mitochondrial dysfunction or oxidative stress and evoke proliferative, inflammatory, and fibrotic reactions, which might impair cardiac electrophysiological characteristics and increase the incidence of cardiac arrhythmia. This study examined the mechanisms how advanced glycation end products may contribute to arrhythmogenesis of right ventricular outflow tract—a unique arrhythmogenic substrate. A whole‐cell patch clamp, conventional electrophysiological study, fluorescence imaging, Western blot, and confocal microscope were used to study the electrical activity, and Ca 2+ homeostasis or signaling in isolated right ventricular outflow tract myocytes with and without advanced glycation end products (100 μg/ml). The advanced glycation end products treated right ventricular outflow tract myocytes had a similar action potential duration as the controls, but exhibited a lower L‐type Ca 2+ current, higher late sodium current and transient outward current. Moreover, the advanced glycation end products treated right ventricular outflow tract myocytes had more intracellular Na +, reverse mode Na + –Ca 2+ exchanger currents, intracellular and mitochondrial reactive oxygen species, and less intracellular Ca 2+ transient and sarcoplasmic reticulum Ca 2+ content with upregulated calcium homeostasis proteins and advanced glycation end products related signaling pathway proteins. In conclusions, advanced glycation end products modulate right ventricular outflow tract electrophysiological characteristics with larger late sodium current, intracellular Na +, reverse mode Na + –Ca 2+ exchanger currents, and disturbed Ca 2+ homeostasis through increased oxidative stress mediated by the activation of the advanced glycation end products signaling pathway. Abstract : Diabetes mellitus is associated with cardiac arrhythmia. Advanced glycation end products (AGE) accumulation in diabetes mellitus may elicit mitochondrial dysfunction/oxidative stress generation and evoke proliferative, inflammatory and fibrotic reactions through AGE‐receptor for AGE (RAGE) signaling pathway, which might impair cardiac electrophysiological characteristics and increases the incidence of cardiac arrhythmias. Our result support that AGEs modulate RVOT electrophysiological characteristics through the activation of AGE‐RAGE signaling pathway with ionic currents modulation, increased intracellular and mitochondrial ROS, and disturbed Ca 2+ homeostasis, which might play a role in diabetes related ventricular arrhythmogenesis and electrical remodeling.